2022
DOI: 10.3390/cimb44100328
|View full text |Cite
|
Sign up to set email alerts
|

The Accelerated Progression of Atherosclerosis Correlates with Decreased miR-33a and miR-21 and Increased miR-122 and miR-3064-5p in Circulation and the Liver of ApoE-/- Mice with Streptozocin (STZ)-Induced Type 2 Diabetes

Abstract: Atherosclerosis is a major risk factor for type 2 diabetes (T2D) mortality. We aim to investigate the changes in miR-21, miR-122, miR-33a and miR-3064-5p in circulation and the liver of ApoE-/- mice with streptozocin (STZ)-induced T2D. Twenty 5-week-old male ApoE-/- mice were randomly assigned to the control (n = 10) and T2D group (n = 10) and intraperitoneally injected with a citrate buffer and streptozotocin (STZ) (40 mg/kg BW) once a day for three consecutive days. The successfully STZ-induced T2D mice (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The levels of miR-146a-5p were high in chronic DFU subjects compared to their acute counterparts, and in endothelial cells exposed to HGM in vitro compared to the control. This finding is in line with other reports where higher levels of miR-146a were reported in DFU and atherosclerosis cases [ 39 , 40 , 41 ]. Contradictory to our data, a lowered expression of miR-146a was assessed which was seen to delay healing response in diabetic mice [ 42 ]; however, few studies have suggested miR-146a as inflammation-inducible miRNA in various disease conditions [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…The levels of miR-146a-5p were high in chronic DFU subjects compared to their acute counterparts, and in endothelial cells exposed to HGM in vitro compared to the control. This finding is in line with other reports where higher levels of miR-146a were reported in DFU and atherosclerosis cases [ 39 , 40 , 41 ]. Contradictory to our data, a lowered expression of miR-146a was assessed which was seen to delay healing response in diabetic mice [ 42 ]; however, few studies have suggested miR-146a as inflammation-inducible miRNA in various disease conditions [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…RNA Isolation, cDNA Synthesis, and Real-Time Fluorescent Quantitative PCR: Preparation of total RNA, cDNA synthesis, and qPCR were performed as described previously. [84] Briefly, total RNA was extracted from the liver and small intestine tissues using the TRIZOL reagent (Invitrogen, USA). Aliquots of 0.5 μg RNA were reversely transcribed to cDNA using the PrimeScript RT reagent kit (Takara, China).…”
Section: Methodsmentioning
confidence: 99%